PENGARUH KEPEMILIKAN PEMERINTAH, LEVERAGE DAN PROFITABILITAS TERHADAP KEBUJAKAN DIVIDEN PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - M. Rizky Ardiansyah; Abd Kodir Djaelani; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to determine the effect of Government Ownership, Leverage, Profitability, and Company Growth, on Dividend Policy. The population in this study were as many as 20 state-owned companies listed on the Indonesia Stock Exchange in 2015-2017. The data used is secondary data from the IDX Financial Reports issued. Samples that meet the criteria standards are 10 BUMN companies. The analysis technique used is linear regression analysis using the SPSS application. The results of the study show partially that government ownership has a negative and significant influence on dividend policy. In this study also found that leverage has a negative and not significant effect on dividend policy. Other variables namely Profitability have a positive and not significant effect on dividend policy. Stimulatively, Government Ownership, Leverage and Profitability have a significant effect on dividend policy. Keywords : Government ownwership, Leverage, Profitability, and Dividend policy.